Performance Enhancement for Wavy Fin Automotive Radiator Using Optimum PG Brine Based Nanofluids - Sahoo R.R.; Ghosh P.; Sarkar J. (My University, 2025)
In this study, optimum propylene glycol (PG) brine-based nanofluids are being proposed as coolants for a wavy finned automotive radiator. Performance analysis is conducted and compared with conventional Ethylene Glycol (EG) brine and related nanofluids. A 25% PG brine has similar heat transfer characteristics to water at higher operating temperature ranges. The effects on radiator size, weight and cost, engine efficiency and fuel consumtion, and embodied energy saving and environmental impact are discussed as well. Compared to conventional coolant(EG water brine), for the same cooling capacity and radiator size, the coolant requirement and pumping power are reduced significantly by about 25% and 64%, respectively, whereas, for the same cooling capacity and mass flow rate, the radiator size and pumping power is reduced by 4.2% and 25.5%, respectively, with PG brine-based Ag nanofluids.Furthermore, by using optimum PG brine-based nanofluids, 3.5% of the embodied energy may be saved, which may yield reductions in radiator cost, engine fuel consumption and environmental costs. © 2016 Wiley Periodicals, Inc.